2020
DOI: 10.1002/jor.24610
|View full text |Cite
|
Sign up to set email alerts
|

Hemiarthroplasty implants should have very low stiffness to optimize cartilage contact stress

Abstract: Hemiarthroplasty is often preferred to total arthroplasty as it preserves native tissue; however, accelerated wear of the opposing cartilage is problematic. This is thought to be caused by the stiffness mismatch between the implant and cartilage‐bone construct. Reducing the stiffness of the implant by changing the material has been hypothesized as a potential solution. This study employs a finite element model to study a concave‐convex hemiarthroplasty articulation for various implant materials (cobalt‐chrome,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…No effect of implanted materials on peripheral blood count parameters and CRP levels were noticed, thus confirming their biocompatibility [ 14 ]. Conversely, Berkmortel et al [ 17 ], when using Bionate-55D, Bionate-75D, and Bionate-80A biomaterials, noted that, in the case of hemiarthroplasty materials, the use of materials with significantly lower stiffness than those currently used was requested [ 17 ]. This confirms the continuous need to search for new solutions in biomaterial implantology.…”
Section: Discussionmentioning
confidence: 99%
“…No effect of implanted materials on peripheral blood count parameters and CRP levels were noticed, thus confirming their biocompatibility [ 14 ]. Conversely, Berkmortel et al [ 17 ], when using Bionate-55D, Bionate-75D, and Bionate-80A biomaterials, noted that, in the case of hemiarthroplasty materials, the use of materials with significantly lower stiffness than those currently used was requested [ 17 ]. This confirms the continuous need to search for new solutions in biomaterial implantology.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mismatch of stiffness between the implant surface and surrounding tissue leads to the damage of the opposing cartilage. [ 154 ] Therefore, in order to maintain the balance between mechanical properties and clinical function, the stiffness of biomedical implants must be optimized to avoid FBR while facilitating adaption between implant and tissue, simultaneously. The relationship between stiffness, porosity, and biocompatibility has been intensively studied, Kelly et al, revealed that both the strength and modulus of the porous Ti implants decreased with the increase of porosity.…”
Section: Implant Physical Characteristics and Fbrmentioning
confidence: 99%